2021
DOI: 10.3390/molecules26195949
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Advances in Anti-Ovarian Cancer with Natural Plants Component

Abstract: Ovarian cancer ranks seventh in the most common malignant tumors among female disease, which seriously threatens female reproductive health. It is characterized by hidden pathogenesis, missed diagnosis, high reoccurrence rate, and poor prognosis. In clinic, the first-line treatment prioritized debulking surgery with paclitaxel-based chemotherapy. The harsh truth is that female patients are prone to relapse due to the dissemination of tumor cells and drug resistance. In these circumstances, the development of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…Along with safety concerns, it is also difficult to meet clinical needs [ 19 21 ]. Pilot studies have shown that TCM, including MAP 30 and Paclitaxel, has been extensively applied to treat ovarian cancer effectively [ 8 10 , 14 ]. However, despite extensive clinical research, the clinical efficacy of TCM is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with safety concerns, it is also difficult to meet clinical needs [ 19 21 ]. Pilot studies have shown that TCM, including MAP 30 and Paclitaxel, has been extensively applied to treat ovarian cancer effectively [ 8 10 , 14 ]. However, despite extensive clinical research, the clinical efficacy of TCM is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine [8][9][10]14]. However, despite extensive clinical research, the clinical efficacy of TCM is still not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural compounds with effective anti-cancer activities are generally active substances extracted from plants and can be classified as glycosides, flavonoids, terpenoids, alkaloids and saponins [ 26 , 27 ]. Most of these compounds exhibit selective inhibition to cancer cells, but show mild toxicity to normal cells, and tolerable side effects to patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a significant global public health issue and has the second highest mortality rate in the United States, accounting for about 610.000 deaths in 2022 . The use of natural plant elements as an alternative to chemotherapy or chemopreventive drugs is an effective strategy in the fight against cancer, especially with the possibility of targeting cancerous cells without healthy cells …”
Section: Introductionmentioning
confidence: 99%